FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU CASH HOLDINGS PADA PERUSAHAAN BESAR DAN PERUSAHAAN KECIL - Syafrizaliadhi, Adhitya Dasha; Arfianto, Erman Denny (Diponegoro Journal of Management, 2014)
Cash is the most liquid assets company that serves as a blood company in the moving operating routine. Failure of firms in the face financial distress has focused attention on the importance of cash holdings. The purposes on this study was to identify relationship between cash holdings and leverage, diversified firms, dividend payment, investment opportunities, bank involvement and size, as well as the behavior cash holdings on big firms and small firms in the manufacturing industry.            This study uses secondary data with data derived from sources IDX and listed company on the Indonesia Stock Exchange during 2 years study period in the 2011 and 2012. Sampling used purposive sampling method with the provisions of the company’s financial reports published during the study period. This study uses two models with the data analysis using the classical assumption, multiple linier regression analysis, t test, F test, the coefficient of determination and Chow Test to distinguish the behavior on a sample of big firms and small firms.            The result showed that the sample of manufacturing firms found negative relationship between cash holdings and leverage. The positive relationship between cash holdings and diversified firms, investment opportunities, bank involvement, and size, but no relationship between capital expenditure, dividend payment and cash holdings. Finally, there is no differences in the behavior of cash holdings between big firms and small firms.